Kantians Defy the Economists' Mantra of Uniform Pigovian Emissions Taxes - Thomas Eichner; Rüdiger Pethig (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper analyzes the efficient emissions taxation in economies with individuals who are morally motivated to reduce their emissions footprint. They are heterogenous with respect to their morality and their consumption preferences. We distinguish between the concepts of moral and conventional utilitarian (= material) welfare. The materially efficient tax rates turn out to be consumer-type specific; they are smaller than the Pigovian tax rate; and the smaller, the higher the individuals' propensity to act morally. Finally, we briefly characterize the second-best uniform emissions tax.
Keywords: H21; Q58; 330; Pigovian tax; material; moral; Kantian; consumer-type tax